Perceived Ease of Use, Usefulness, and Social Influence as Determinants of Consumer Purchase Intention - Cahyani Kurniastuti; Ismayudin Yuliyzar; Putra Pratama; Eko Sulistio (Prosiding University Research Colloquium, 2026)
This study investigates the influence of perceived ease of use, perceived usefulness, and social influence on consumers’ behavioral intention to purchase Nike footwear, with a focus on users based in Lippo Karawaci, Tangerang. A quantitative research design was employed using a structured questionnaire administered to 100 respondents who had previously purchased or used Nike shoes. The results indicate that all three independent variables exert a significant and positive effect on behavioral intention, with social influence emerging as the strongest predictor. The proposed model explains 92.5 percent of the variance in consumer purchase intention, demonstrating substantial explanatory power. These findings highlight the pivotal role of social dynamics such as peer influence and brand related social identity in shaping consumer decision-making in the global sportswear market. The study contributes theoretically by extending the application of the Technology Acceptance Model (TAM) to a non-digital product context, and practically by offering actionable insights for lifestyle brand marketing strategies, particularly in relation to influencer engagement and brand community development.